2019
DOI: 10.1007/s00211-019-01046-6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of quasi-Monte Carlo methods for elliptic eigenvalue problems with stochastic coefficients

Abstract: We consider the forward problem of uncertainty quantification for the generalised Dirichlet eigenvalue problem for a coercive second order partial differential operator with random coefficients, motivated by problems in structural mechanics, photonic crystals and neutron diffusion. The PDE coefficients are assumed to be uniformly bounded random fields, represented as infinite series parametrised by uniformly distributed i.i.d. random variables. The expectation of the fundamental eigenvalue of this problem is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(60 citation statements)
references
References 36 publications
(72 reference statements)
2
58
0
Order By: Relevance
“…In this section we briefly summarise the relevant material on variational EVPs, two-grid FE methods and QMC methods. For further details we refer the reader to the references indicated throughout or to [19].…”
Section: Mathematical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…In this section we briefly summarise the relevant material on variational EVPs, two-grid FE methods and QMC methods. For further details we refer the reader to the references indicated throughout or to [19].…”
Section: Mathematical Backgroundmentioning
confidence: 99%
“…The Krein-Rutmann Theorem ensures that the smallest eigenvalue is simple, and then in [19,Prop. 2.4] it was shown that the spectral gap can be bounded away from 0 independently of y.…”
Section: Variational Eigenvalue Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…This global normalization constraint in fact makes the problem nonlinear as opposed to its deterministic counterpart. Moreover, current mathematical analysis (see, e.g., [4,7]) is based on second-order model problems where it is guaranteed that the smallest mode is well-isolated and hence the question of subspace convergence is still not resolved and is the subject of current research.…”
Section: Introductionmentioning
confidence: 99%
“…As an example of the important role that the spectral gap plays in error analysis, consider the random elliptic eigenvalue problem from [8]. There, an algorithm using dimension truncation, Quasi-Monte Carlo (QMC) quadrature and finite element (FE) methods was used to approximate the expectation with respect to the stochastic parameters of the smallest eigenvalue.…”
Section: Introductionmentioning
confidence: 99%